Javanese Language Reduplication in Pinggir District, Bengkalis Regency - Prida Asriani; Alber (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
Research on the form of Reduplication of the Javanese language in Pinggir District, Bengkalis Regency was carried out with the aim of describing and analyzing the form and meaning of Javanese Reduplication in Pinggir District, which is starting to become extinct because the younger generation is embarrassed to use it. It is hoped that this research can provide knowledge, especially to the younger generation, to understand the importance of the role of the Javanese language in preserving the Javanese language in Pinggir District, Bengkalis Regency. This research approach is a qualitative approach with ethnographic methods. Meanwhile, the data source for this research is Javanese speech obtained through interviews with three Javanese-speaking informants in Pinggir District. Research data regarding the form and meaning of Javanese language reduplication in Pinggir District, Bengkalis Regency. Researchers identified 121 forms of Javanese language reduplication, which were categorized into four types: complete repetition (51 repetitions), partial repetition (6 repetitions), repetition combined with affixing processes (59 repetitions) and repetition of phoneme changes (5 repetitions). 121 utterances, including reduplication which expresses the meaning 'many' (36 examples) not found reduplication which expresses the meaning 'unconditional', reduplication expresses a meaning which resembles what is said in the basic form, done repeatedly', done at will, with casually, or happily, carried out by two parties and regarding each other' (52 examples), reduplication states 'work-related matters' (7 examples), reduplication states the meaning 'somewhat' (3 examples), reduplication states the meaning ' the highest attainable level' (8 examples), expressed 'intensity of feeling' (15 examples). It turns out that people in Pinggir District are more likely to use repetitive speech combined with the process of adding affixes and speech that expresses the meaning of 'actions that are done repeatedly' in everyday life